Cardiac considerations in the operative management of the patient with Duchenne or Becker muscular dystrophy. Issue 9 (19th July 2013) - Cripe, Linda H.; Tobias, Joseph D.; Brandom, Barbara
Summary Duchenne muscular dystrophy/Becker muscular dystrophy (DMD/BMD) is a progressive multisystem neuromuscular disorder. In addition to the skeletal muscle, the myocardium in the DMD/BMD patient is dystrophin deficient which results in a progressive cardiomyopathy. The myopathic myocardium poses significant risk of increased morbidity and mortality at the time of major surgical procedures. Careful attention must be given to the DMD/BMD patient during the intraoperative and postoperative period. Anesthesia selection is critical and anesthetics should be avoided which have been shown to be harmful in this patient population. Preanesthesia assessment should include cardiac consultation and detailed preoperative evaluation. Intraoperative management needs to insure that the weakened myocardium is not compromised by physiologic changes such as hypotension or major fluid shifts. Finally, attention to the cardiac status of the patient must continue into the postoperative period. The surgical care of the DMD/BMD patient requires a multispecialty approach to insure operative success.